Poly (vinyl alcohol) based carbon nanofibers as freestanding anodes for lithium‐ion batteries - Pampal, Esra Serife; Stojanovska, Elena; Kilic, Ali; Demir, Ali (Wiley, 2024)
Abstract In this study, we investigated the iodination process for the preparation of water‐soluble polyvinyl alcohol (PVA)‐based carbon nanofibers (CNFs) and their electrochemical properties. Iodinated nanofibers were carbonized at different temperatures (600°C, 800°C) under an argon (Ar) atmosphere. Morphology and physical properties of fiber mats were characterized by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy, and thermogravimetric analysis (TGA), while electrical conductivity measurements were done using four probes. As a freestanding anode in half‐cell lithium batteries, the CNFs were prepared by electrospinning of PVA and PVA–CNT blend, which was exposed to iodine vapor at various temperatures (60, 80, and 100°C). Iodine vapor treatment at 80°C and subsequent carbonization at 800°C provided a 29% carbon yield. The resulting CNT‐containing optimized CNFs exhibited superior flexibility, electrical conductivity (2.16 S/cm), and handleability, making them a promising, binder‐free environmentally friendly carbon source for lithium‐ion batteries with high capacity (672 mAh/g at 50 mA/g). The study clearly showed that PVA might be an alternative precursor for the production of carbon micro‐ and nanofibers. Highlights Anodic performance of PVA‐based carbon nanofibers was analyzed. PVA precursor offers economic and environmental option for binder‐free electrodes. PVA–CNT composite nanofibers with optimized iodination and carbonization time identified as a promising high carbon yield carbon source for lithium‐ion batteries. CNT‐containing optimized carbon nanofibers exhibited superior flexibility and electrical conductivity (2.16 S/cm). Freestanding fiber anodes exhibited a higher capacity of 672 mAh/g, at 50 mA/g compared to conventional graphite anode (372 mAh/g).